Transient shuttle for a widespread neural probe with minimal perturbation - Roh, Yeonwook; Kim, Hyeongseok; Kim, Eun A.; Ji, Kyungbin; Kang, Minji; Gong, Dohyeon; Im, Sunghoon; Hong, Insic; Park, Jieun; Park, Soo Jung; Bae, Yiseul; Park, Jae Il; et al. (npj Flexible Electronics, 2024)
Bioelectronic implants in the deep brain provide the opportunity to monitor deep brain activity with potential applications in disease diagnostics and treatment. However, mechanical mismatch between a probe and brain tissue can cause surgical trauma in the brain and limit chronic probe-based monitoring, leading to performance degradation. Here, we report a transient shuttle-based probe consisting of a PVA and a mesh-type probe. A rigid shuttle based on PVA implants an ultrathin mesh probe in the target deep brain without a tangle, while creating both a sharp edge for facile penetration into the brain and an anti-friction layer between the probe and brain tissue through dissolving its surface. The capability to shuttle dissolved materials can exclude the retracted process of the shuttle in the brain. Complete dissolution of the shuttle provides a dramatic decrease (~1078-fold) in the stiffness of the probe, which can therefore chronically monitor a wide area of the brain. These results indicate the ability to use a simplistic design for implantation of wide and deep brain probes while preventing unnecessary damage to the brain and probe degradation during long-term use.